2019
DOI: 10.1136/bmjopen-2018-024747
|View full text |Cite
|
Sign up to set email alerts
|

Unintended discontinuation of medication following hospitalisation: a retrospective cohort study

Abstract: ObjectivesWhether unintended discontinuation of common, evidence-based, long-term medication occurs after hospitalisation; what factors are associated with unintended discontinuation; and whether the presence of documentation of medication at hospital discharge is associated with continuity of medication in general practice.DesignRetrospective cohort study between 2012 and 2015.SettingElectronic records and hospital supplied discharge notifications in 44 Irish general practices.Participants20 488 patients aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…There is a signi cant body of evidence in the Irish context that the omission of medications from discharge prescriptions and discharge summaries has an impact on patient care, and is therefore a strong marker of iatrogenic risk [2,3,[5][6][7][8][10][11][12]. This study found that a multi-component educational intervention had a small effect on improving prescribing errors and communication at discharge.…”
Section: Resultsmentioning
confidence: 72%
“…There is a signi cant body of evidence in the Irish context that the omission of medications from discharge prescriptions and discharge summaries has an impact on patient care, and is therefore a strong marker of iatrogenic risk [2,3,[5][6][7][8][10][11][12]. This study found that a multi-component educational intervention had a small effect on improving prescribing errors and communication at discharge.…”
Section: Resultsmentioning
confidence: 72%
“…All the aforementioned variables also negatively influence long-term adherence, which has further been shown to decline due to poor health literacy, cognitive or psychic impairment, and medication cost issues (among others) [18][19][20][21]. Long-term adherence to APT has been reported to decline substantially over time [17,22,23,24,25,26,27,28], but more favourable results have also been reported [5,6,10,12,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The REporting of studies Conducted using Observational Routinely-collected health Data (RECORD) statement was used in the conduct and reporting of this retrospective cohort study. [24] Setting and data source Data were collected as part of a larger study from 44 general practices in the Republic of Ireland in the areas of Dublin (n=30), Galway (n=11) and Cork (n=3) using the patient management software Socrates (www.socrates.ie) between January 2011 and 2017 [25,26]. Data, anonymised at the time of extraction, included demographic, clinical, prescribing and hospitalisation records of patients who were 65 years and older at the date of data extraction (2017).…”
Section: Methodsmentioning
confidence: 99%